A long-term responding epidermal growth factor receptor mutated non-small cell lung cancer patient with extremely high mutation allele frequency - Miyazaki, Kunihiko; Sato, Yoshiharu; Satoh, Hiroaki; Hizawa, Nobuyuki (Contemporary Oncology/Współczesna Onkologia, 2022)
Epidermal growth factor receptor (EGFR) mutation is the most frequent oncogenic driver in non-small cell lung cancer (NSCLC) [1, 2]. Among EGFR mutations, exon 19 deletion and exon 21 L858R are two of the most common mutations; hence they are referred to as common mutations [1]. In addition to them, there are many types of EGFR mutation other than common mutations. They are treated as uncommon mutations [3, 4]. Recent advances in analysis technology using next-generation sequencing (NGS) have made great progress also in the area of EGFR mutation [5–8]. By this analytic method, it has become clear that there is heterogeneity among patients with common mutations. Among these possible heterogeneities, mutation allele frequency (MAF) has drawn attention [9–13]. MAF is defined as the number of times a mutated base is observed, divided by the total number of times any base is observed at the locus. It corresponds to the percentage of sequencing reads that contain the mutation, and the proportion of alleles is affected by the proportion of tumor cells in the sample and the presence of copy number alterations [9–13]. Here we report a case of a patient with EGFR mutation with very high MAF, who responded to EGFR-tyrosine kinases for a long time.